The Effectiveness of Differentiated Learning Approach within PBL Model to Improve Students’ Critical Thinking Skills - Agusmaliani, Agusmaliani; Pelenkahu, Noldy; Oroh, Elisabeth Z. (English Education Department, 2025)
This study aims to determine the effectiveness of the Differentiated Learning Approach within the Problem-Based Learning (PBL) model in improving students’ critical thinking skills in English, particularly on the topic of analytical exposition text among grade XI students of SMA Negeri 2 Tondano. This study employed a quantitative method using a quasi-experimental design of the Non-Equivalent Group Design type. The sample consisted of class XI A as the experimental group and XI B as the control group, each with 20 students selected through random sampling. Data collection techniques included pre-test, post-test, observations, and documentation. Data were analyzed using the t-test to examine the effect off Differentiated Learning approach within PBL to students’ Critical Thinking. The results revealed a significant difference between the experimental and control classes. Students in the experimental group who received instruction using the Differentiated Learning Approach within the PBL model showed notable improvement. The average pre-test score in learning achievement increased from from 58.45 to 83.20. The t-test showed a significance value of 0.000 (< 0.05. These findings demonstrate that the Differentiated Learning Approach within the Problem-Based Learning model is effective in enhancing students' critical thinking skills, particularly in learning English analytical exposition texts.